Sosialisasi Pemilahan Sampah “Bersih Itu Keren” Di SD 2 Jegu, Tabanan, Bali - Nur Aprilya, Fira; Dwi Sanjani Mertaningsih, Ni Kadek; Lin, Fanny; Wardhiana, Nyoman Dana; Oktavia Gama, Adie Wahyudi; Lestara Permana, Gusi Putu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Garbage has become a problem that is often found in today's environment. Especially in Jegu Village, Penebel District, Tabanan Regency, Bali Province, there is a waste problem that is quite worrying if it is not immediately handled with the right solution. In addition to having a negative impact on the environment and health, waste will also have a negative impact on the economy in Jegu Village. Starting from small things, namely providing an understanding to elementary school children about the importance of the role of children in maintaining cleanliness. The author approaches and educates by conducting socialization at Jegu 2 Elementary School with the theme "Clean is Cool" which will provide learning about how easy it is to sort waste and keep the surrounding environment clean. Conducting counseling in 3 classes at Elementary School 2 Jegu and there are 40 elementary students who are correspondents in this report. before the socialization was held, there were 35 students who knew the correct waste sorting concept and there were 5 students who did not understand the concept. With this socialization, it is hoped that in the future the children will bring positive changes to cleanliness in Jegu Village.